Interview with Manuel Stetter (Nordic Journal of Practical Theology, 2024)
This is an interview with professor in practical theology at the University of Rostock, Manuel Stetter, about his research on funeral practices. The interview is conducted by professor Tone Stangeland Kaufman, Oslo.
Keywords: Funeral practices.; Materiality; Body; Embodiment